Pembuatan Company Prodile Berbasisi Web Pada Pinarax Shoe - Perani Rosyani; Arief Rahman (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In today's online era, the technique of sellers waiting for customers to come to physical stores is still common. However, the sales system that is widely used by the community today is less successful in reaching consumers because it requires consumers to come to a physical store and inspect the goods directly. Most shops still use banners and brochures to promote their services; However, this method is less effective in promoting services because banners or brochures usually do not include service specifications clearly, and this kind of promotion model requires a large amount of funds. Based on these problems, the author wants to design a web based sales system design that can contain products to be marketed in detail with all specifications and can be seen by all internet users. This sales system will be developed by direct observation, this method will facilitate the design and process before the system is built. The result of using this method is a Web-Based Company Profile. This Marketing Information System can later be used by sellers and buyers in conducting transactions.